Islamic perspective on marketing mix - Ishak, Mohd. Shuhaimi; Abdullah @ Chuah Hock Leng, Osman (The Social Sciences Research Society, 2012)
Islam is a religion that has economic and business systems that are well defined and have proven their efficacy and strength. In fact, Islam is a religious faith which cannot be separated from the realities of daily human activities, either religiosity, social or commercial. Given the scenario that commercial transactions are part and parcel of human daily activities, Islam provides a framework that shapes the moral and ethical behaviour of all commercial endeavours. Islamic teachings cover all commercial transactions, whether international or local. In marketing practices, Islamic teachings embedded in the Quran and the traditions of the Prophet (saw) have a foundation that is based on equity and justice. With this in mind, the paper attempts to identify the salient characteristics of the Islamic perspective on the framework of marketing mix. The paper analyses the five Ps of marketing mix which are product, price, promotion, place and people from the perspective of Islam. The paper adopts the methodology of evaluating the prevailing practices of marketing mix from an Islamic perspective with the sole aim to highlight the efficacy and strength of an Islamic ethical framework. Finally, the paper illustrates that Islam provides a framework for the creating and sustaining of a strong ethical marketing culture.